1993
DOI: 10.1007/bf02319011
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient utilization in liquid/membrane system for watermelon micropropagation

Abstract: Watermelon [Citrullus lanatus (Thunberg) Matsumura and Nakai] proliferating shoot meristems from established shoot cultures were inoculated on modified Murashige and Skoog salts medium supplemented with 10 txM 6-benzyladenine (BA) for shoot proliferation and on similar medium supplemented with 1 IxM BA and 10 txM gibberellic acid (GA3) for shoot elongation. Agar-solidified medium and microporous polypropylene membrane rafts in liquid medium were used to support the tissues. Growth over culture time of prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 18 publications
1
6
0
2
Order By: Relevance
“…Plant micropropagation systems on liquid medium associated to membrane rafts has been successfully used in several works (Watad et al, 1995;Desamero et al, 1993;Adelberg et al, 1992). However, as far as we know this is the first report describing the use of such system for somatic embryogenesis induction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant micropropagation systems on liquid medium associated to membrane rafts has been successfully used in several works (Watad et al, 1995;Desamero et al, 1993;Adelberg et al, 1992). However, as far as we know this is the first report describing the use of such system for somatic embryogenesis induction.…”
Section: Resultsmentioning
confidence: 99%
“…On plant micropropagation studies, this culture system has shown better results when compared to cultures conducted on either liquid and solid medium (Hew et al, 1990;Young et al, 1991;Desamero et al, 1993;Watad et al, 1995). However, it has never been tested in studies on induction and regeneration of somatic embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Os estudos sobre os requerimentos nutricionais de plantas in vitro visam otimizar o crescimento das culturas, como também relacionar a taxa de crescimento com a absorção dos elementos do meio (Desamero et al, 1993 ) seria razoável supor que meios de cultura com concentrações menores sejam suficientes para sustentar o crescimento celular.…”
Section: Discussionunclassified
“…(Al-Sayed y Ahmend 2013), vitaminas (Desamero et al 1993), micronutrientes esenciales y citrulina El principal interés científico de la citrulina es que se encuentra presente en tres vías metabólicas diferentes: como intermediario del ciclo de la urea en el hígado, como productor de la enzima sintasa (necesaria en la producción de óxido nítrico) y como sintetizador da Arginina (Curis et al 2005;Romero et al 2006). Además la citrulina tiene gran poder antioxidante (Fang et al 2002), siendo eficiente eliminador de radicales hidroxilos (Akashi et al 2001), y se utilizada como relajante y como vasodilatador para reducir la fatiga y dolores musculares producido por el ácido láctico después del esfuerzo físico (Tarazona et al 2011), y tiene función nutricional para los ancianos (Piñeiro et al 2010), dentro de otras propiedades benéficas a la salud.…”
Section: Introductionunclassified